Phonon thermal conductivity limited by electron scattering in amorphous Zr70Cu30 - Esquinazi, P.; de la Cruz, F. (American Physical Society, 1983)
Fil: Esquinazi, P. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina; Universidad Nacional de Cuyo; Argentina